MEDIA TERHADAP PENINGKATAN NIAT BERTINDAK DAN PERSEPSI KESEHATAN GIGI - Donny Triwahyudi (Eduhealth, 2015)
ABSTRACTThe problem of the teeth is a health problem that is still experienced by developed countries and developing countries including Indonesia. According to data Riskesdas in 2013 aged 10-14 years 25.2 %. One is the level of individual dental hygiene. Age 10-12 years of age who are prone to dental problems The aim of this study was to analyze the differences in media posters on the intention to act and perception. This study uses a pre experimental research with one group pretest - posttest . Research methods with total sampling . Methods of statistical analysis with Whitney test , p = < 0.05 . A significant value of p = 0.000 directing that there are different intention to act after the treatment . Is expected for the next researcher to develop in the direction of action.Key words : Poster, intention to act, perseption, dental hygieneABSTRAKMasalah gigi merupakan masalah kesehatan yang masih dialami negara maju maupun negara berkembang termasuk Indonesia. Menurut data Riskesdas tahun 2013 usia 10-14 tahun 25,2%. Salah satunya adalah tingkat kebersihan gigi individu. Usia 10-12 tahun merupakan usia yang rawan terjadinya masalah gigi Tujuan dari penelitian ini adalah menganalisis perbedaan media poster terhadap niat untuk bertindak dan persepsi. Penelitian ini mengunakan penelitian pra eksperimen dengan one group pretest